Hepatitis C virus genotype 3: a genotype that is not 'easy-to-treat'. (March 2015) - Buti, Maria; Esteban, Rafael
<x xml:space="preserve">Abstract</x> The efficacy of antiviral treatment depends on which of the seven genotypes (G1–G7) of hepatitis C virus (HCV) has infected the patient. Conventionally, clinicians regarded G2 and G3 infections as 'easy-to-treat': dual therapy with pegylated interferon and ribavirin produces a sustained virologic response in approximately 40–50% of patients with G1 infection, compared with 80% when analyses report combined data for G2 and G3 patients, which is standard practice in many clinical studies. However, sustained virologic response rates appear to be lower in certain subgroups of people infected with G3 compared with those with G2 or the general HCV-infected population. This review examines the growing evidence that factors related to the virus (e.g., baseline viral load and a rapid virologic response) and host characteristics (e.g., steatosis and fibrosis, metabolic syndrome, host polymorphisms and ethnicity) contribute to variations in therapeutic success in G3 HCV.